Understanding Consumption Pattern of Rural and Urban Consumers in Malaysia - Sulaiman, Yaty; Mat, Nik Kamariah Nik; Ghani, Noor Hasmini Abd; Arif, Alysha (International Journal of Engineering and Technology, 2018)
The consumption pattern of Malaysian consumers has changed markedly since 2005 as shown by several indicators such as consumer price index, per capita income and inflation rate. Instability of economy, increased in food prices, political stability, employment, debt, work life balance, increased in utility bills and fuel prices, health and crimes become major concerns for Malaysian consumers especially in urban areas to be more cautious in their spending. This study attempts to examines the factors contributing to consumption model for Malaysian consumers in rural and urban areas. From the literature, eight antecedents of Malaysian consumption pattern were identified. Consumer lifestyle, consumer value, consumer motive, consumer preference, and marketing mix of price, product, place, and advertising were measured using 7-point Likert scales. From 1400 questionnaires distributed to households, 851 were returned representing 61 percent response rate. The findings indicate support for validity of measurement models of all variables utilized for both model rural and urban. Using Structural Equation Modeling (SEM) of SMARTPLS 2.0 technique, it was found that advertising is not a predictor for consumer motive for both model, rural and urban.Â Apart of that, the reason of price hikes has been discussed. On the other hand, rural model postulates better R2 than the other model. The finding implies that Malaysian government need to continuously campaign for consumers about the implementation of GST and its consequences for consumers. In addition, the instability of economic changed the consumption pattern throughout their lifestyle, value, motive and preferences.Â